Ducklings - Sexton, Colleen A. (Minneapolis, Minn. : Bellwether Media, 2008)
"A basic introduction to ducklings. Simple text and full color photographs. Developed by literacy experts for students in kindergarten through third grade"--Provided by publisher.
Keywords: Ducklings